The Antecedent of Domestic Investment in Indonesia: Auto Regressive Distributed Lag Approach - Pramudita, Thomas Galih; Indartono, Setyabudi; Sholeh, Maimun (International Journal of Economics and Financial Issues, 2019)
Investment is one of the important factor in a developing country’s economy such as Indonesia which really needs the flow of investment to create jobs. The Investment comes from two sources, namely foreign investment and domestic investment. However, the foreign investment can cause problems for national companies in helping the country’s economic development if there is no strict regulation from the government. These obstacles come from the financial of foreign investment as the sources to fund the long-term. Therefore, it is important for the government to empower domestic investment as one of the income sources in establishing an equitable economy. Although the current Indonesian economic situation has shown a positive direction, domestic investment growth has not shown a satisfactory increase yet. This problem for Indonesia, which currently more focuses on the growth of the national industry. Thus, this study aims to determine the determinants of macroeconomic variables on the development of domestic investment in Indonesia in the period 1996 - 2017. The method used in this study is the Auto Regressive Distributed Lag (ARDL) method. The results showed that inflation and interest rates had no effect on long run but had effect on a short-run in domestic investment. While the exchange rate had effect on both short and long-run in domestic investment and economic growth had effect on long run in domestic investment. Keywords: Macroeconomic Variables, Domestic Investment, ARDL JEL Classifications: E22, E43, O55 DOI: https://doi.org/10.32479/ijefi.7545